Na casa das onças: xamanismo e performance na antropologia de E. Jean Langdon - Laura Pérez Gil; Luciana Hartmann (Journal de la Société des Américanistes)
Raised and educated in the United States, Esther Jean Langdon conducted intensive field research among the Siona (Western Tukanoan), in the Colombian Amazon and has worked, for the last four decades, at the Universidade Federal de Santa Catarina, in the south of Brazil. In this article, we look over her intellectual production and emphasize resonances among the subjects around which her work is articulated: indigenous health, shamanism, and performance. From these considerations, we highlight the main concepts—practice, dialogicity and emergence—that characterize her theoretical and ethnographical contributions.